Shariah governance framework for Islamic co-operatives as an integral social insitution in Malaysia - Ismail, Muhammad Issyam; Hassan, Rusni; Syed Jaafar Alhabshi, Syed Musa (International Islamic University Malaysia, 2016)
In Malaysia, Islamic cooperatives are recognized as providers of some form of Islamic financial service similar to Islamic Banks and Takaful Operators. An Islamic Co-operative refers to a co-operative conducting activities and businesses based on Shariah principles. Being a non-banking financial institution, its main objective is to enhance social economic welfare of its members. As a form of captive social institution, it enables the less economically privileged members of society to pool resources as a cooperative. Malaysia is spearheading the Islamic banking and finance industry globally by having in place a proper and well-designed legal and regulatory framework for Islamic Financial Institutions, which includes the area of Shariah governance. However, the Shariah governance framework for the Islamic Co-operative in Malaysia is still in its infancy stage. In this paper, this area will be given focus and properly highlighted. Later, comparison will be made with the Shariah governance framework for the Islamic financial institutions. This paper will conclude that the requirements with regard to Shariah governance for the Islamic Co-operative are flexible and not as strict as required for the Islamic financial institutions.